Penerapan Teknologi Olah Sampah di Sumber (TOSS) dalam Pengelolaan Sampah Rumah Tangga pada Bank Sampah PKH Kepompong di Kecamatan Mungka - Veronika Sriwulantari; Heri Faisal Harahap; Idris Idris (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
Solid waste management in Indonesia still faces a major service gap, as reflected by open dumping, open burning, and disposal into water bodies. In Lima Puluh Kota Regency, 81.57% of the 2024 waste generation was reported as unmanaged, while the Payakumbuh Regional Landfill became inoperable following an explosion and landslide in late 2023. This community service program aimed to strengthen the capacity of the PKH Kepompong Waste Bank in Jorong Sopan to manage household organic waste through Source-Based Waste Processing Technology (TOSS). The program employed a sequence of activities: awareness-raising on source segregation, introduction to the TOSS workflow, and hands-on training on producing eco-enzyme from fruit waste as a bio-activator, followed by composting practice using a 30×30×30 cm bamboo box. A total of 37 waste bank members participated, with an emphasis on practical skill development. The results indicate that participants improved their understanding of organic–inorganic segregation, were able to prepare eco-enzyme, and practiced composting so that decomposed material could be harvested as compost. Key enabling factors included the post-landfill disruption urgency, the waste bank’s institutional support, and simple locally available materials; constraints involved consistent segregation, moisture/aeration control, and the eco-enzyme fermentation period. Simple SOPs, community monitors, and basic indicator recording are recommended to sustain routine adoption. TOSS implementation has the potential to reduce open burning and river dumping, minimize odors and flies, and divert the dominant organic fraction into inputs for home gardening. Compost can be used for household gardens or marketed locally.